2009
DOI: 10.1039/b816375h
|View full text |Cite
|
Sign up to set email alerts
|

Localised to intraligand charge-transfer states in cyclometalated platinum complexes: an experimental and theoretical study into the influence of electron-rich pendants and modulation of excited states by ion binding

Abstract: The neopentyl ester of 1,3-di(2-pyridyl)benzene-5-boronic acid (dpy-B) is a useful intermediate in the divergent synthesis of N;C;N-coordinating, 1,3-di(2-pyridyl)benzene ligands, HL(n), that carry aryl substituents at the 5-position of the central ring. The platinum(ii) complexes, PtL(n)Cl, of several such ligands have been prepared, incorporating pendant anisoles, arylamines, an oxacrown, and an azacrown, all of which are strongly luminescent in solution at 298 K. The emission of the complexes is partially q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 62 publications
2
61
0
Order By: Relevance
“…1) show intense bands in the region 260-330 nm, which can be assigned to intraligand 1 p-p* transitions of cyclometallated 1,3-di(2-pyridyl)benzene 21 and acetylide 18 ligands, and less intense bands at 330-450 nm, corresponding to transitions of mixed charge-transfer/ligandcentred character. 28 Although the substitution of the chloride ligand by the phenylacetylide does not change the spectral profile substantially, the individual bands in this region become rather less wellresolved, and there is evidence of a tail to longer wavelength in the phenyl acetylide complexes. This might tentatively be attributed to the introduction of a p C^C / p* N^C^N ligand-toligand charge-transfer (LLCT) transition, by analogy with other Pt(II) acetylide complexes, 10,11,18 and as suggested by the observed trend in oxidation potentials discussed above, which indicate that the HOMO is raised in energy upon introduction of the acetylide.…”
Section: Photophysical and Electrochemical Properties In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) show intense bands in the region 260-330 nm, which can be assigned to intraligand 1 p-p* transitions of cyclometallated 1,3-di(2-pyridyl)benzene 21 and acetylide 18 ligands, and less intense bands at 330-450 nm, corresponding to transitions of mixed charge-transfer/ligandcentred character. 28 Although the substitution of the chloride ligand by the phenylacetylide does not change the spectral profile substantially, the individual bands in this region become rather less wellresolved, and there is evidence of a tail to longer wavelength in the phenyl acetylide complexes. This might tentatively be attributed to the introduction of a p C^C / p* N^C^N ligand-toligand charge-transfer (LLCT) transition, by analogy with other Pt(II) acetylide complexes, 10,11,18 and as suggested by the observed trend in oxidation potentials discussed above, which indicate that the HOMO is raised in energy upon introduction of the acetylide.…”
Section: Photophysical and Electrochemical Properties In Solutionmentioning
confidence: 99%
“…All four complexes show a similar reduction peak around À2.3 V. The lack of significant variation with the co-ligand or central aryl substituent is consistent with the lowest unoccupied molecular orbital (LUMO) being dominated by the pyridyl rings, with little contribution expected from the cyclometallating ring or co-ligand. 28 On the other hand, the introduction of the phenylacetylide co-ligand is seen to shift the oxidation potential significantly to less positive potentials for both pairs of complexes, suggesting that the strongly s-donating acetylide ligand raises the energy of the highest occupied molecular orbital (HOMO). Density functional theory calculations have previously suggested that the HOMO in [Pt(N^C^N) Cl] complexes is spread over the metal, the co-ligand, and the cyclometallating aryl ring.…”
Section: Photophysical and Electrochemical Properties In Solutionmentioning
confidence: 99%
“…Typically in complexes such as Pt(dpyb)Cl, the bands in the 350 -400 nm region have ε values of around 7000 M , with no counterparts in the proligands, and are due to metal--to--ligand and intra--ligand charge--transfer transitions that are introduced upon cyclometallation. 30,47,48 Such transitions will necessarily be present in the current complexes, but they are evidently superimposed by intense ligand--centred transitions. This leads to unusually high ε values in this region.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Meanwhile, the change in the monomeric co-ligand from chloride in MePtCl to isothiocyanate in MePtNCS is seen to have essentially no significant effect, probably reflecting the rather small participation of the co-ligand in such complexes, 27 and the similar positions of the NCS and Cl ligands in the spectrochemical series.…”
mentioning
confidence: 99%
“…Thus, timedependent density functional theory calculations on HPtCl have revealed that the T 1 state has predominantly HOMO-LUMO character. 27 The HOMO is based primarily on the aryl ring, the metal ion and the chloride co-ligand, whilst the LUMO is predominantly localised on the pyridyl rings. The inductive electron-withdrawing effect of F atoms, irrespective of whether they be meta or para to the metal, should lower the energy of both HOMO and LUMO, as found, for example, with iridium (III) complexes containing related fluorine-substituted terdentate ligands.…”
mentioning
confidence: 99%